Sisters Brothers Pack Heat : or How the Sisters Fared in the West - Polić-Jurković, Vanja (Array, 2014)
The article analyzes Patrick deWitt’s Governor General’s Award-winning novel The Sisters Brothers (2011) with respect to its adherence and deviation from the cowboy western genre. The article explores the context of the novel: it starts with the juxtaposition of the real historical spaces of the western North American continent and the Wild West myth which was created as the open spaces of wilderness started to decline and the North American continent was colonized from the east coast to the west. The Wild West myth is generally taken to emerge with F. J. Turner’s “frontier thesis” which observes the American West as frontier and no-man’s land but also as a process that created the American civilization as separate and independent from the imperial European civilization. The attractiveness of the Wild West myth is explored and its role in fulfilling the need for a national myth or a creation story of the US. The tropes of the Wild West are briefly discussed, such as typical landscapes, climate and typical characters, among which presides the figure of the cowboy, observed again from the perspective of the function and importance of the Wild West myth in the popular imaginary of the North Americans. In the main part of the article the novel’s place within the cowboy western genre is analyzed, its stereotypical traits and its idiosyncrasies which stretch the generic confinements but do not break them, such as the paradoxical title ; the novel’s self-reflexivity where the first person narrator creates his own legend ; protagonists who are villains but also sensitive cowboys ; unexpected ending ; introspective narrator ; ironic and humorous style of narration sympathetic to the brothers, as well as the only possible exceptions to the genre, uncanny elements such as visions and witches.The article concludes that the novel is a contemporary reinvention of the cowboy western.